USE OF CLOUD TECHNOLOGIES IN EDUCATION - Issabayeva, Д.Н.; Shekerbekova, Ш.Т. (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2020)
The article describes the advantages of the use of cloud technologies in training and theoretical researches of the scientific literature. "Cloud technology" appeared in a result of evolution of information technology over the last decade. The term "cloud technology" frequently found in scientific and technical literature. This term denotes a model of network access on-demand to a common set of configurable computing resources (network, servers, storage, applications, services) that can be quickly prepared for work; wherein the part of the user requires minimal interaction with the service provider, just having a computer device having access to the Internet. The idea of using "cloud technology" in the course of training, transfer of educational-methodical documentation, theoretical and practical exercises in the Internet is literally "in the air". Cloud computing has a great future, so all who are close to IT should master this technology